The effects of thiamine inhibition on ruminal fermentation: a preliminary study - Ungerfeld, E M; Rust, S R; Burnett, R (Folia microbiologica, 2009)
Inhibition of methanogenesis in ruminal cultures was attempted by hindering thiamine availability through its degradation by 'polyphenols' and competition for active sites on enzymes and transporters using thiamine structural analogs. Effects on fermentation were small and not consistently reversed by adding thiamine. Lack of major effects of the compounds evaluated could be due to intracellular synthesis of thiamine covering most requirements.
Keywords: Fermentation; Methane; Thiamine; thiamin; Rumen; zvířata; skot; fermentace; bachor; methan; Cattle; Animals